2018
DOI: 10.1103/physrevlett.120.141803
|View full text |Cite
|
Sign up to set email alerts
|

No-Go Theorem for Nonstandard Explanations of the τKSπντ

Abstract: The CP asymmetry in τ → K S πν τ , as measured by the BABAR collaboration, differs from the standard model prediction by 2.8σ. Most nonstandard interactions do not allow for the required strong phase needed to produce a nonvanishing CP asymmetry, leaving only new tensor interactions as a possible mechanism. We demonstrate that, contrary to previous assumptions in the literature, the crucial interference between vector and tensor phases is suppressed by at least 2 orders of magnitude due to Watson's final-state… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
210
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(227 citation statements)
references
References 78 publications
12
210
5
Order By: Relevance
“…[21,28,29], the tensor form factor was assumed to be a real constant, which is motivated by the analysis of K 3 (K → π ν with = e, µ) data [16], and the relative strong phase, being now just the phase of the vector form factor, was found to be large enough to produce a sizable CP asymmetry. This assumption was, however, pointed out to be incorrect by Cirigliano, Crivellin and Hoferichter [24]. They demonstrated that, as the same spin-1 resonances contributing to the vector form factor will equivalently contribute to the tensor one, the crucial interference between vector and tensor phases is suppressed by at least two orders of magnitude due to Watson's final-state-interaction theorem [30], and the amount of CP asymmetry that a tensor operator can produce is, therefore, strongly suppressed [24].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…[21,28,29], the tensor form factor was assumed to be a real constant, which is motivated by the analysis of K 3 (K → π ν with = e, µ) data [16], and the relative strong phase, being now just the phase of the vector form factor, was found to be large enough to produce a sizable CP asymmetry. This assumption was, however, pointed out to be incorrect by Cirigliano, Crivellin and Hoferichter [24]. They demonstrated that, as the same spin-1 resonances contributing to the vector form factor will equivalently contribute to the tensor one, the crucial interference between vector and tensor phases is suppressed by at least two orders of magnitude due to Watson's final-state-interaction theorem [30], and the amount of CP asymmetry that a tensor operator can produce is, therefore, strongly suppressed [24].…”
Section: Introductionmentioning
confidence: 99%
“…This assumption was, however, pointed out to be incorrect by Cirigliano, Crivellin and Hoferichter [24]. They demonstrated that, as the same spin-1 resonances contributing to the vector form factor will equivalently contribute to the tensor one, the crucial interference between vector and tensor phases is suppressed by at least two orders of magnitude due to Watson's final-state-interaction theorem [30], and the amount of CP asymmetry that a tensor operator can produce is, therefore, strongly suppressed [24].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…We translate the result of shall rely on theoretical considerations only. The key observation is that the tensor form factor admits an Omnès dispersive representation [35,37,38,64,65]. We thus write the general two-meson ( ′ ) tensor form factor as…”
Section: Scalar Contributionsmentioning
confidence: 99%